Analisis Pelaksanaan Penanganan Tindak Pidana Korupsi Di Kabupaten Ogan Komering Ilir - Sandy, Amiruddin; Syuroh, Mat; Sutioso, Sutioso (@-Publik: Jurnal Administrasi Publik, 2021)
The purpose of this study is to analyze the analysis of applications for handling corruption in Ogan Komering Ilir Regency. This research is a qualitative research. Data or news is collected through interviews with informants. The result of the research shows that the analysis of the implementation of the Handling of Corruption Crimes in Ogan Komering Ilir Regency has been realized although there are still some obstacles. The following will present some conclusions as a result of the origin of the research activities as follows. based on the dimensions of Planning, the lack of available funds, and inadequate personnel capabilities due to mutations or rolling personnel. Another obstacle is the unavailability of facilities and infrastructure, such as the absence of tools for tracking telephone numbers from suspected corruption. According to the organizational dimension, the lack of coordination is one error using the Corruption Eradication Commission (Corruption Eradication Commission) which results in frequent clashes between law enforcement agencies, where all feel they have a share in a corruption crime. according to the dimensions of the Movement, socialization has been carried out through counseling, banners, through regional radio, information letters and through broadcasts or advertisements broadcast on television. Then the application of activities for handling corruption crimes has been carried out in accordance with existing mechanisms. based on the dimension of supervision, internal control has been carried out in stages in accordance with the organizational structure through tight evaluation of activities, briefings, direct supervision and through written reports. External supervision is carried out by the Election Eradication Commission (Corruption Eradication Commission), through personal introductions and online media. Citizens also as social control comes from handling corruption.